The construction of environmental participation in South Africa - (:unkn) unknown (My University, 2017)
Since the 1980s, participatory processes have proliferated all over the world, without having enabled for a democratization of political systems. While the adoption of such processes is often thought has an imperative, in particular for developing countries and in the environmental field, this thesis seeks to explain the construction of environmental participation in South Africa, using an approach aiming at identifying the actors involved, analyzing their motivations and the way in which they influence it. Our analytical framework offers to study the behavior of groups of actors through four dimensions: the competition between political actors; the weight of administrative structures; the profile of professionalized service providers; the struggles of social actors. Our study relies on semi-structured interviews, meetings’ observations, grey literature and the collect of records. At the end of our thesis, we notice little interest from political actors for environmental participatory processes in South Africa. This causes a lack of incentive for administrative structures to take the public voice into account, usually leading to a low-cost organization by consultants, which does only allow for a monitory of the South African population to express itself. Civil servants who do not have the support of administrative structures with which they should collaborate try nonetheless to circumvent them by seeking public support so that they can implement their mandate for environmental preservation. In order to make their way into the South African participation market dominated by environmental consultants, independent consultants also choose to specialize themselves into the public participation field and to favor the organization of participatory processes adapted to the local context.
Keywords: African Research